2008
DOI: 10.1136/bjo.2007.132746
|View full text |Cite
|
Sign up to set email alerts
|

British Oculoplastic Surgery Society (BOPSS) National Ptosis Survey

Abstract: The authors have generated a valid series of surgical outcomes both for individuals, units and the UK as a whole, expressed in both objective and subjective terms for what we regard as the signature procedure for an oculoplastic surgeon: aponeurotic ptosis surgery. Individual results have been communicated to our members, which will allow them to compare their results with true peer-group-generated figures and will aid appraisal and ultimately revalidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 14 publications
3
32
0
Order By: Relevance
“…11,12 The average time needed to operate for each eyelid was 31.1 min, which was comparable with the average time of 26.3 min reported by Frueh et al 13 using the small incision, minimal dissection anterior approach procedure. In contrast, the same author reported an average time of 56.6 min for traditional lid crease incision approach.…”
Section: Discussionsupporting
confidence: 72%
“…11,12 The average time needed to operate for each eyelid was 31.1 min, which was comparable with the average time of 26.3 min reported by Frueh et al 13 using the small incision, minimal dissection anterior approach procedure. In contrast, the same author reported an average time of 56.6 min for traditional lid crease incision approach.…”
Section: Discussionsupporting
confidence: 72%
“…More recently, a BOPSS national survey reported that only 57% of patients undergoing primary aponeurotic surgery in the United Kingdom had a successful outcome with 65% of patients completely satisfied with the results. 1 There is only one comparative study of anterior levator advancement vs MMCR for the correction of involutional ptosis, which reported a 22% lower revision rate for MMCR vs anterior levator advancement and a statistically better cosmetic outcome. 15 This is consistent with other reports of Muller's muscle resection, which suggest a generally higher success rate (85-98%) compared with that for anterior approach levator advancement.…”
Section: Resultsmentioning
confidence: 99%
“…Levator aponeurosis surgery was first advocated by Jones et al 14 for the treatment of involutional ptosis, and since then, reported success rates in the literature have varied, ranging from 57 to over 90%. [1][2][3][4] In a large series of anterior levator advancement, McCulley et al 2 found that 77% of eyelids were symmetrical to within 1 mm of the fellow eye, with 8.8% of eyelids requiring re-operation. More recently, a BOPSS national survey reported that only 57% of patients undergoing primary aponeurotic surgery in the United Kingdom had a successful outcome with 65% of patients completely satisfied with the results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocular hypotelorism was defined as a reduced ICD and OCD, and ocular hypertelorism as an increased distance of the ICD and OCD (Feingold & Bossert 1974). The distance from the upper eyelid margin to the corneal reflex distance (UMRD) was measured to establish the presence of ptosis, defined as an UMRD £ 2 mm, or if there was a ‡2 mm asymmetry between the two eyes (Scoppettuolo et al 2008) and also if the PFW was below reference values (Greenberg & Prein 2002). All these measurements were classified as abnormal if the values were <2 SD.…”
Section: Methodsmentioning
confidence: 99%